Locality and Local Gazetteers in the Republic: A Case for the Continuity of Spatial Order. Issue 1 (January 2023) - Du, Yongtao
Abstract: The way late imperial political elites in China positioned themselves in the tianxia —their life world—can be described as a balance between polity and locality, which was often accompanied by an enduring sense of local identity. This article argues that despite the fall of the tianxia concept in modern China, the age-old locality–polity relationship and the elite local identity did not disappear. Taking the flourishing local gazetteer production of the Republican era as a case, I suggest that instead of suppressing locality, the crisis of the polity and the coming of the nation-state in China brought it more to the foreground. The decline of locality in China's political culture occurred only after the communist takeover. The study makes use of the Local Gazetteer Research Tools (LoGaRT) developed by Max Planck Institute for the History of Sciences.